Assessment of the Level of Radioactivity in the Soil in Urban Areas and Building Materials of Arlit City (Agadez-NIGER) - Sidibé, M. O.; Manga, A. O.; Soumana, S.; Adukpo, O. K. (National Research and Innovation Agency, 2024)
Niger's uranium deposits are located in the north, bordering the southern Sahara. Mining activities led to the creation of the town of Arlit in 1969. Uranium mining and uranate production generate large volumes of radioactive solid and liquid tailings, as well as radioactive gases. Through dispersion and transport, these radioactive discharges become a source of contamination to the environment and food chain. The aim of our work is to assess the additional ambient exposure to radioactivity of surrounding populations as a result of mining activities. We assessed the risk of exposure to radionuclides from the uranium-238 decay chain through soil and certain building materials. The methodology used is based on collection of soil, sand, gravel and mud samples, which are analyzed using gamma spectrometry technique. Nine (9) public sites and five (5) building materials quarries were sampled for the work. The radiological parameters calculated are radium equivalent activity (Raeq), absorbed dose rate (D), internal and external risk indices (Hin and Hex) and gamma index (Iγ). For the whole study area, the calculated Raeq values range from 78.67 Bq/kg to 199.32 Bq/kg. These values are below the guideline value of 370 Bq/kg. In terms of air dose rate, however, the average value found was 0.32 mSv/year for the nine public sites considered. This exceeds the threshold value of 0.29 mSv/year corresponding to the selected exposure scenarios. In addition, in the mud (Quarry 5) and the second gravel quarry (Quarry 4), Iγ values greater than unity were found. A comparison is made with the results of similar studies around the world. Interpretation of the data obtained concludes that there is a risk of radiological overexposure at six (6) sites and two (2) quarries. This work is independent research which sheds new light on the issue of uranium mining activities impact on the environment in Arlit.